Review papers U1-RNP and Toll-like receptors in the pathogenesis of mixed connective tissue disease Part II. Endosomal TLRs and their biological significance in the pathogenesis of mixed connective tissue disease - Agnieszka Paradowska-Gorycka (Rheumatology, 2015)
Mixed connective tissue disease (MCTD) is a chronic autoimmune immunopathological disease of unknown etiology, which is characterized by the presence of various clinical symptoms and the presence of autoantibodies against U1-RNP particles. The U1-RNP component engages immune cells and their receptors in a complex network of interactions that ultimately lead to autoimmunity, inflammation, and tissue injury. The anti-U1-RNP autoantibodies form an immune complex with self-RNA, present in MCTD serum, which can act as endosomal Toll-like receptor (TLR) ligands. Inhibition of TLRs by nucleic acids is a promising area of research for the development of novel therapeutic strategies against pathogenic infection, tumorigenesis and autoimmunity. In this review we summarize current knowledge of endogenous TLRs and discuss their biological significance in the pathogenesis of MCTD. In part I we described the structure, biological function and significance of the U1-RNP complex in MCTD.